Engaging willing consumers: international cases and trends - Neidhardt, Harald (Henry Stewart Talks, 2009)
Disruption in mobile markets, Mobile market data, Mobile ecosystem, Fragmentation rules mobile, The 4 E's, Messaging, Outdoor integration and innovation, Mobile rich media content, China case study, Mobile viral marketing, Smartphones on the rise
Archived at 2022/04/11